Representation of Islamic Values in the Korean Drama Man Who Dies to Live - Salsabila, Arini; Zainuddin, Mahli (Journal of Islamic Communication and Counseling, 2022)
The film is one of the mass media that has the potential to influence audiences. Moreover, the film has more power than just entertainment media. It is able to oppose, reinforce and even overturn a religious perspective, basic values, and ideological assumptions. This study aimed to determine how the representation of Islamic teachings in the Korean drama Man who dies to live. This research applied a descriptive qualitative approach. The object of research was the whole drama Man who dies to live, while the subjects were the scenes in the film that interpret the teachings of Islam. The data analysis technique used Charles Sanders Pierce's semiotic analysis through the triadic method by identifying signs, objects, and interpretations. The result showed that several teachings of Islam are incompatible with those depicted in the drama man who dies to live, such as the use of hijab, foods, congregational prayers, and invitations to commit immorality.